PENGARUH MARKETING MIX TERHADAP KEPUTUSAN MEMBELI MOTOR HONDA SCOOPY DI SAMARINDA - Pratama, Shendy (EKONOMIA, 2014)
The purpose of marketing is to influence events for the buyer is willing to buy the product at the time the consumer requires. To be able to influence buyer behavior manufacturers need to know how that would be targeted sales . By knowing the buyer behavior manufacturer can decide how the product will be sold .To analyze the effect of independent variables ( the marketing mix ) to the buying decision, then used multiple linear regression models .Four independent variables of the Marketing Mix a positive influence on Buying Decisions ( Y ) of Honda Scoopy , which produces regression equation is Y = 0.039 + 0.775 X1 - 0.005 X2 - 0.276 X3 + 0.429 X4.Coefficient of determination or R2 of 0.856 or 85.6 % which shows the ability of the independent variables explain the dependent variable was 85.6 % , while the remaining 14.4 % is explained by other variables in addition to the variables in the model . R value of 0.925 Model Summary table , or by 92.5 % . It is clear that the models used are very decent .Â